Proportional-Resonant Controller Structure with Finite Gain for Three-Phase Grid-Tied Converters - Marek Nowak; Tomasz Binkowski; Stanisław Piróg (Energies, 2021)
The paper presents the study of a three-phase system coupling a DC power source to a power grid. This study, based on an FPGA, implements a real-time control system and digital models of the power circuit. The proposed proportional–resonant (P+R) controller with a modified structure was part of the system, which can be used as an alternative controller to traditional ones, e.g., in photovoltaic systems. Due to difficulties in implementing resonant controllers, a P+R with a new structure using a PI controller was elaborated. With an appropriate approach to the generation of phase current patterns, it is possible to set the reactive current and, thus, compensate for the reactive power. The operation of the system for typical operating conditions (e.g., system startup, change in preset load) was characterized and compared with a classical solution using a PI controller.